Awareness about prostate cancer and early diagnosis as a way to contribute to Blue November in an organization in the interior of Western São Paulo: An experience report (International Seven Journal of Health Research, 2024)
Introduction: Prostate cancer (AC) is the most morbidity and mortality of men in developed countries, being the main cause of cancer among men and the second cause of mortality in Brazil (1). It has a slow clinical development and its incidence increases with age. Early detection of prostate cancer is essential to prevent potential damage (2). It is known that prostate-specific antigen (PSA) is a tumor marker capable of early detection of prostate AC (3), however, due to its sensitivity and specificity, it should not be used as the only diagnostic tool. Thus, digital rectal examination plays an important role in helping the early detection of this patient (4). Objective: To promote awareness about men's health, related to the prevention and early diagnosis of prostate cancer, in the context of the national Blue November campaign. Description: Students of the fifth term of medicine at the University of Western São Paulo went to the Life Squad in order to raise awareness about Blue November and present a lecture on men's health, in addition to carrying out health promotion actions for the men residing there. Initially, the listeners were directed to an auditorium, where the lecture was given and there was a moment to clear up doubts. After that, blood glucose tests and blood pressure measurements were done, as well as rapid tests for sexually transmitted infections. The students were responsible for identifying the patient and filling out the questionnaire necessary for such exams, while the nursing team present performed the tests and communicated the results. Conclusions: These actions are extremely important for men's health, in view of the low knowledge about prostate AC and the benefits of prior diagnosis. Thus, early detection prevents complications, increases patient survival, and offers psychosocial support.